Cost-effectiveness of financial incentives to improve glycemic control in adults with diabetes: A pilot randomized controlled trial. - Leonard E Egede; Rebekah J Walker; Clara E Dismuke-Greer; Sarah Pyzyk; Aprill Z Dawson; Joni S Williams; Jennifer A Campbell (PLoS ONE)
Purpose Determine the cost-effectiveness of three financial incentive structures in obtaining a 1% within group drop in HbA1c among adults with diabetes. Methods 60 African Americans with type 2 diabetes were randomized to one of three financial incentive structures and followed for 3-months. Group 1 (low frequency) received a single incentive for absolute HbA1c reduction, Group 2 (moderate frequency) received a two-part incentive for home testing of glucose and absolute HbA1c reduction and Group 3 (high frequency) received a multiple component incentive for home testing, attendance of weekly telephone education classes and absolute HbA1c reduction. The primary clinical outcome was HbA1c reduction within each arm at 3-months. Cost for each arm was calculated based on the cost of the intervention, cost of health care visits during the 3-month time frame, and cost of workdays missed from illness. Incremental cost effectiveness ratios (ICER) were calculated based on achieving a 1% within group drop in HbA1c and were bootstrapped with 1,000 replications. Results The ICER to decrease HbA1c by 1% was $1,100 for all three arms, however, bootstrapped standard errors differed with Group 1 having twice the variation around the ICER coefficient as Groups 2 and 3. ICERs were statistically significant for Groups 2 and 3 (p<0.001) indicating they are cost effective interventions. Conclusions Given ICERs of prior diabetes interventions range from $1,000-$4,000, a cost of $1,100 per 1% within group decrease in HbA1c is a promising intervention. Multi-component incentive structures seem to have the least variation in cost-effectiveness.